2020
DOI: 10.1093/treephys/tpaa018
|View full text |Cite
|
Sign up to set email alerts
|

The PalERF109 transcription factor positively regulates salt tolerance via PalHKT1;2 in Populus alba var. pyramidalis

Abstract: Salinity restricts the growth of trees to varying extents, but the regulatory mechanisms involved in their varying salt tolerance are largely unknown. In an effort to elucidate these mechanisms, we identified a total of 99 genes in the Ethylene Responsive Factor (ERF) family of transcription factors and examined their expression patterns under salt stress in Populus alba var. pyramidalis. We found that a B4 group gene, PalERF109, was rapidly induced by salt treatment and preferentially expressed in stems and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…JERF36s belong to the ERF transcription factor class, which are involved in signal transduction, hormone synthesis, and stress responses (Li et al, 2009;Zhang and Huang, 2010;Su et al, 2011). Previous researches have demonstrated that ERF transcription factors could enhance stress resistance in A. thaliana, N. tabacum, Lilium longifloruma, and Populus (Gilmour et al, 2000;Wang et al, 2004;Li et al, 2006;Li et al, 2009;Su et al, 2011;Yao et al, 2016;Yao et al, 2017;Charfeddine et al, 2019;Chen et al, 2020;Jiang et al, 2020). Expression of JERFs activates the expression of resistanceassociated genes and promotes the ability of plants to adapt to environmental stress.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…JERF36s belong to the ERF transcription factor class, which are involved in signal transduction, hormone synthesis, and stress responses (Li et al, 2009;Zhang and Huang, 2010;Su et al, 2011). Previous researches have demonstrated that ERF transcription factors could enhance stress resistance in A. thaliana, N. tabacum, Lilium longifloruma, and Populus (Gilmour et al, 2000;Wang et al, 2004;Li et al, 2006;Li et al, 2009;Su et al, 2011;Yao et al, 2016;Yao et al, 2017;Charfeddine et al, 2019;Chen et al, 2020;Jiang et al, 2020). Expression of JERFs activates the expression of resistanceassociated genes and promotes the ability of plants to adapt to environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of ERF76 in transgenic poplar upregulated the expression of 16 transcription factor genes and 45 stress-related genes and also increased the ability of ABA and GA (gibberellic acid) biosynthesis, which resulted in stronger tolerance to salt stress (Yao et al, 2016). Overexpression of PalERF109 increased the transcript abundance of salt stressrelated genes, enhanced the ABA signaling pathway, and induced expression of salt many ion channel proteins as well as transporters in transgenic poplars with higher salt tolerance (Chen et al, 2020). Plant hormones and plant hormone signaling pathways regulate complex signaling networks related to plant development and responses to environmental stresses (Bari and Jones, 2009;Zhu, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations